Phononic crystal based sensor to detect acoustic variations in methyl & ethyl nonafluorobutyl ether. (August 2022) - Muhammad
Abstract: Phononic crystals and metamaterials have been widely studied for wave manipulation applications. In this study, we propose a conceptual framework for a new type of acoustic bio-chemical sensor that works based on the principle of phononic crystals and metamaterials to detect the temperature and pressure changes in active solvents like Methyl Nonafluorobutyl Ether (MNE) and Ethyl Nonafluorobutyl Ether (ENE). First, a wide low-frequency bandgap is obtained from the proposed composite unit cell structure with trampoline effect. Then a defect is introduced to adjust the localize cavity modes inside the reported bandgap. Later, the cavity is filled with MNE and ENE solvents that eventually resulted into fluid-solid coupling physics. The numerical wave dispersion curves and transmission profiles show presence of Fano-like interference/resonance effect evident from the observation of asymmetrical transmission profile. Such robust asymmetrical transmission peak is generated due to coupling of incident waves with scattered wave field emitted from the MNE and ENE solvents upon excitation. The variation in acoustic properties of MNE and ENE caused by temperature and pressure fields on newly born Fano-like asymmetrical transmission profile is studied. The proposed acoustic bio-chemical sensor governed by Fano-interference effect efficiently capture the variation in acoustic properties of MNE and ENE solvents at relatively low-frequency regime that makes this approach favorable for sensing applications. Such smart acoustic bio-chemical sensors can have useful applications in pharmaceutical production, petrochemicals and capturing ingredients of cosmetic and beauty products. Graphical Abstract: ga1